Altered driving performance of symptomatic Huntington's disease gene carriers in simulated road conditions. (3rd October 2018) - Jacobs, Milou; Hart, Ellen P.; Miranda, Yuri Mejia; Groeneveld, Geert Jan; van Gerven, Joop M. A.; Roos, Raymund A. C.
Abstract: Objective: In clinical practice, patients with Huntington's disease (HD) often decide to solely drive in their own familiar neighborhoods and not on a motorway or in an unknown area. The aim of the study was to identify differences in driving performance between HD gene carriers and healthy individuals in simulated urban and motorway environments. Methods: This cross-sectional study included 87 participants (28 premanifest HD, 30 manifest HD, 29 controls). All participants were active drivers and were assessed using a driving simulator, a driving history questionnaire, and the Unified Huntington's Disease Rating Scale. The driving simulator session included urban and motorway scenarios. Analysis of variance and Kruskal-Wallis tests were used to compare urban and motorway driving across all 3 groups. Results: Manifest HD drove slower compared to controls and premanifest HD when speed limits increased (80 and 100 km/h) and they had a less steady speed compared to premanifest HD on the motorway and in a 30 km/h zone. Manifest HD also had a larger standard deviation of the lateral position (i.e., more weaving of the car/less vehicle control) compared to controls and premanifest HD on the motorway. Conclusions: Manifest HD drive more cautious in a driving simulator when speed limits increase compared to premanifest HD and controls and they have less vehicle control on the motorway. The driving simulator parameters are able to discriminate between manifest HD and healthy individuals, so a driving simulator seems a feasible tool to use when investigating changes in driving in manifest HD.